'Techlash', responsible innovation, and the self-regulatory organization. Issue 2 (4th May 2019) - Hemphill, Thomas A.
ABSTRACT: In 2018, major social media companies became the focus of a 'techlash' in America. The business practices of Facebook, Google, Amazon, and Twitter came under intensive media and U.S. government scrutiny on a range of troubling issues, including wielding monopoly power, facilitating fake news, violating consumer privacy, and involvement in Russian disinformation campaigns during the 2016 U.S. Presidential election. An alternative private ordering approach to incorporating responsible innovation is proposed in lieu of public regulation: the self-regulating organization (SRO). A recent HarrisX poll found that only 31% of U.S. adults believe that the federal government is capable of regulating large technology companies; this provides an opportunity for the tech industry to develop an effective SRO. Yet, to be successful it will require a high degree of organizational transparency and accountability, and trade-offs made among the competing values of various industry stakeholders, including consumers, government representatives, small tech companies, civil society organizations and advocacy groups.